The Acute Effect of Dynamic vs. Proprioceptive Neuromuscular Facilitation Stretching on Sprint and Jump Performance - Cik Nor Fazila Abd Malek, Ali Md Nadzalan (Tanjung Malim, 2024)
The Acute Effect of Dynamic vs. Proprioceptive Neuromuscular Facilitation Stretching on Sprint and Jump Performance by Cik Nor Fazila Abd Malek, Ali Md Nadzalan